Comprehensive Evaluation of Commercial Bisulfite-Based DNA Methylation Kits and Development of an Alternative Protocol With Improved Conversion Performance. (22nd March 2018) - Tierling, Sascha; Schmitt, Beate; Walter, Jörn
DNA methylation is the most studied epigenetic modification with a wide range of regulatory functions in mammalian genomes. It almost exclusively resides on CpG dinucleotides and, among others, plays important roles in early embryo development, onset, and maintenance of cancer. During the past 3 decades, many approaches have been developed to discriminate methylated from unmethylated DNA including antibody-based enrichment of methylated DNA, restriction enzyme-based, or hybridization-based methods. The conversion of unmethylated cytosines to uracils by sodium or ammonium bisulfite is regarded as golden standard as this approach requires no enzymatic reaction and provides deep and reliable insight in methylation patterns at single-base resolution. Nowadays, there are many commercial kits for bisulfite conversion available but they perform differently and also vary in protocols and chemicals used. Here, we provide the first comprehensive and comparative evaluation of bisulfite conversion kits observing major differences in conversion efficiency and DNA degradation which greatly affect the performance of downstream applications, ie, polymerase chain reactions (PCRs). Moreover, deep sequencing of amplicons containing oxidized derivates of 5ʹ-methylC shows that none of the tested kits efficiently converts 5ʹ-formylC without substantial conversion of 5ʹ-methylC or 5ʹ-hydroxymethylC. Consequently, we developed a robust and easy-to-use protocol that allows maximal discrimination between 5ʹ-formylC and 5ʹ-methylC/5ʹ-hydroxymethylC with low DNA degradation and high PCR efficiency on the bisulfite-treated DNA. We highly recommend to use our time- and cost-efficient protocol for any genome-wide or local high-resolution bisulfite sequencing application to minimize conversion-dependent error rates.